THE EFFECT OF ETHANOL EXTRACT OF SOURSOP LEAVES (ANNONA MURICATA L.) ON BODY TEMPERATURE IN MALE MICE (MUS MUSCULUS) INFECTED WITH BACTERIA SALMONELLA TYPHI - Syarifuddin, Aminah; Cahya, Cucu Arum Dwi; Br Sihombing, Amelya Chyntia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Soursop leaves (Annona muricata L.) are a plant that has many health benefits that can be obtained from the fruit, leaves, and seeds. Soursop leaves contain saponins, flavonoids, tannins, and alkaloids which can act as an antiseptic-disinfectant or as an antibacterial. Flavonoid compounds can be used as wound medicine, antifungal, antimicrobial, anticancer, and antiviral. In society, it is used by boiling the leaves and then drinking the boiled water. This research aims to determine the effectiveness of soursop leaf ethanol extract as an antibacterial against Salmonella typhi so that fever can be reduced. The dosage includes 100; 150; 200; and 250 mg/kg BW. No treatment was given as a negative control and chloramphenicol tablets as a positive control. Based on data analysis, it shows that there is a significant difference in body temperature after being tested using the t-test with a value of 0.000 < 0.05. These results prove that body temperature which was initially normal during the acclimatization stage experienced an increase in body temperature when infected with Salmonella typhi. The results of the One-Way ANOVA test also showed an effect on reducing body temperature infected with Salmonella typhi. From several doses, the EDDS dose of 100 mg/kg BW was able to reduce body temperature by an average of 36.5°C.